2017
DOI: 10.12688/f1000research.9636.1
|View full text |Cite
|
Sign up to set email alerts
|

Alport syndrome: facts and opinions

Abstract: In this commentary, I review recent advances in Alport syndrome genetics, diagnostics, and therapeutics. I also offer some opinions regarding strategies to optimize the early identification of affected individuals to promote early therapeutic intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 66 publications
(64 reference statements)
1
37
0
5
Order By: Relevance
“…Although ADAS was thought to be an extremely rare disease and its disease concept was unclear for a long time, recent studies clarified genetic, clinical, and pathological features [6]. Furthermore, due to the rapid development of comprehensive genetic analysis technique using next-generation sequencing (NGS), it has been revealed that the number of patients with chronic kidney disease (CKD) caused by these gene mutations is far higher than previously expected [9][10][11][12], resulting in ongoing discussions regarding the diagnosis of this condition [13][14][15][16][17]. Here, we review the previous publications regarding TBMN and ADAS and discuss the diagnosis of cases with heterozygous COL4A3 or COL4A4 variants.…”
Section: Introductionmentioning
confidence: 99%
“…Although ADAS was thought to be an extremely rare disease and its disease concept was unclear for a long time, recent studies clarified genetic, clinical, and pathological features [6]. Furthermore, due to the rapid development of comprehensive genetic analysis technique using next-generation sequencing (NGS), it has been revealed that the number of patients with chronic kidney disease (CKD) caused by these gene mutations is far higher than previously expected [9][10][11][12], resulting in ongoing discussions regarding the diagnosis of this condition [13][14][15][16][17]. Here, we review the previous publications regarding TBMN and ADAS and discuss the diagnosis of cases with heterozygous COL4A3 or COL4A4 variants.…”
Section: Introductionmentioning
confidence: 99%
“…94 Anterior lenticonus that results from inability of the lens to hold its shape can result in myopia. 95,96 Though the exact mechanism of SNHL in AS is yet undetermined, bilateral progressive high-frequency loss is seen in most cases. [95][96][97] In X-linked males, 50% have some hearing loss at age 15 and 90% have hearing loss by age 40.…”
Section: Alport Syndromementioning
confidence: 99%
“…95,96 Though the exact mechanism of SNHL in AS is yet undetermined, bilateral progressive high-frequency loss is seen in most cases. [95][96][97] In X-linked males, 50% have some hearing loss at age 15 and 90% have hearing loss by age 40. 98 Early hearing loss often portends worse renal damage.…”
Section: Alport Syndromementioning
confidence: 99%
“…Unbehandelt führt das Alport-Syndrom häufig in der zweiten bis dritten Lebensdekade zu einer dialysepflichtigen chronischen Nierenerkrankung. Neuere Daten deuten dagegen auf einen sehr guten Verlauf unter Therapie mit einem ACE-Hemmer hin [19,20]. Grundlage der Erkrankung ist ein Defekt der Kollagensynthese mit Veränderungen u. a. der glomerulären Basalmembran.…”
Section: Nephrotisches Syndromunclassified